Роль 3d моделювання у відтворенні історичних об'єктів та артефактів у віртуальних музеях - Панченко, А. О. (ХНУРЕ, 2024)
This work is devoted to the study of the role of 3D modeling in the repro duction of historical objects and artifacts in virtual museums, namely, their use for the study and research of historical objects without their physical damage, allows you to preserve historical artifacts for future generations, reducing the risk of their loss or damage. In addition, with the help of 3D modeling, historical objects can be recreated in a realistic scale and detail, which gives visitors a unique experience. This opens up new opportunities for studying history and culture and makes them accessible to a wide audience through virtual museums.
Keywords: віртуальний музей; відтворення історичних об'єктів